2018
DOI: 10.1007/s10637-018-0641-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity of various peritoneal cancer cell lines to HIPEC and PIPAC: comparison of an experimental duplex drug to standard drug regimens in vitro

Abstract: We performed an in-vitro study testing the chemosensitivity of peritoneal cancer cell lines (SW620, HCT116, MKN45, 23,132/87, OAW42) to various cytostatic drug regimens. A duplex drug, characterized by reversible linking of the antimetabolites 2'-deoxy-5-fluorouridine (5-FdU) and 3'-C-ethynylcytidine (ECyd), was compared to oxaliplatin or to cisplatin plus doxorubicin. The experiments were designed to reflect the conditions of intraperitoneal chemotherapy. CASY® (Cell Analysis System) technology was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The therapeutic benefit of HIPEC has been limited by various factors, such as inefficient drug penetration and resistance to standard chemotherapy drugs. [8,10,14,47] In this study, we quantified the drug delivery efficiency of HIPEC at the cellular level using single-cell ICP-MS, and found that, compared with small sized tumors, larger tumors are associated with limited drug penetration ( Figure 2). To improve drug delivery to tumors, we developed a novel delivery system through fusion of genetically engineered exosomes and thermosensitive liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic benefit of HIPEC has been limited by various factors, such as inefficient drug penetration and resistance to standard chemotherapy drugs. [8,10,14,47] In this study, we quantified the drug delivery efficiency of HIPEC at the cellular level using single-cell ICP-MS, and found that, compared with small sized tumors, larger tumors are associated with limited drug penetration ( Figure 2). To improve drug delivery to tumors, we developed a novel delivery system through fusion of genetically engineered exosomes and thermosensitive liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the locoregional administration of pressurized aerosol drugs, it maximizes exposure of peritoneal tumor implants to chemotherapy agents, with favorable pharmacokinetics and biodistribution, as demonstrated in several pre-clinical studies. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Overall, the search identified: 23 stage 0 studies; 18 stage 1 studies and two protocol papers for stage 1 studies; 25 stage 2a studies, one protocol paper and five trial registrations (NCT01854255, NCT02735928, NCT03246321, NCT02604784 and NCT03124394) for stage 2a studies; six stage 2b studies and three protocol papers for stage 2b studies; and three protocol papers for stage 3 studies. Fig .…”
Section: Resultsmentioning
confidence: 99%